2011
DOI: 10.1038/ncb2314
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic stem cells require Wnt proteins to prevent differentiation to epiblast stem cells

Abstract: Pluripotent stem cells exist in naive and primed states, epitomized by mouse embryonic stem cells (ESCs) and the developmentally more advanced epiblast stem cells (EpiSCs; ref. 1). In the naive state of ESCs, the genome has an unusual open conformation and possesses a minimum of repressive epigenetic marks2. In contrast, EpiSCs have activated the epigenetic machinery that supports differentiation towards the embryonic cell types3–6. The transition from naive to primed pluripotency therefore represents a pivota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
419
3
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(446 citation statements)
references
References 39 publications
12
419
3
1
Order By: Relevance
“…Early analyses of Wnt reporters or immunostaining for stabilized, nonphosphorylated b-catenin failed to detect active canonical Wnt signaling in the embryos at this stage (Mohamed et al 2004). However, a recent study, using a different Wnt reporter, revealed a transient activation of Wnt signaling in the ICM, which is extinguished on implantation (ten Berge et al 2011). Consistent with this observation, this recent study also found that Wnt signaling activation is required to maintain the undifferentiated state of ICMderived embryonic stem cells in vitro (ten Berge et al 2011).…”
Section: Implantationsupporting
confidence: 73%
See 2 more Smart Citations
“…Early analyses of Wnt reporters or immunostaining for stabilized, nonphosphorylated b-catenin failed to detect active canonical Wnt signaling in the embryos at this stage (Mohamed et al 2004). However, a recent study, using a different Wnt reporter, revealed a transient activation of Wnt signaling in the ICM, which is extinguished on implantation (ten Berge et al 2011). Consistent with this observation, this recent study also found that Wnt signaling activation is required to maintain the undifferentiated state of ICMderived embryonic stem cells in vitro (ten Berge et al 2011).…”
Section: Implantationsupporting
confidence: 73%
“…Earlier studies attributed this defect to a more severe disruption of Cripto expression in b-catenin -/-mutants, because Cripto is a presumptive transcriptional target of b-catenin and a Nodal coreceptor essential for AVE migration (Ding et al 1998;Morkel et al 2003). However, Cripto expression is earlier and much broader than Wnt reporter expression that marks b-catenin induced transcriptional activity (Mohamed et al 2004;ten Berge et al 2008). Furthermore, in bcatenin GOF mutants, Cripto is highly expressed yet the AVE fails to form (Morkel et al 2003).…”
Section: E65mentioning
confidence: 96%
See 1 more Smart Citation
“…The combination of LIF þ ERK inhibitor without GSK3 inhibitors was able to support self-renewal of cells, albeit with a significantly lower efficiency than 2i conditions (Ying et al 2008;Wray et al 2011). Similarly, ERK inhibitors could be omitted when LIF was added together with GSK3 inhibition or recombinant Wnt3a (Ying et al 2008;Berge et al 2011;Wray et al 2011). Indeed, some reports show that the positive effect of Wnt/b-catenin signaling on self-renewal is substantially greater than that of ERK inhibition (Berge et al 2011).…”
Section: Wnt Signaling Stimulates Long-term Self-renewal Of Naive Mescsmentioning
confidence: 99%
“…Again, some emphasize the importance of canonical Wnt signaling for differentiation [166,167], while others suggest the opposite [59,[168][169][170]. This could be partially More recently, mES cell differentiation was found to be accompanied by activation of noncanonical signaling via increased expression of Tcf3 [171], which is known to signal independently of -catenin in several contexts [172].…”
Section: Human Neural Stem and Progenitor Cells: Intracellular Componmentioning
confidence: 99%